Development of two measures of client engagement for use in home aged care. (26th February 2015) - Baker, Jess Rose; Harrison, Fleur; Low, Lee‐Fay
Abstract: The aim of the study was to develop and validate measures of client engagement in aged homecare. The Homecare Measure of Engagement‐Staff questionnaire (HoME‐S) is a self‐complete measure of six dimensions of client engagement: client acceptance, attention, attitude, appropriateness, engagement duration and passivity. The Homecare Measure of Engagement‐Client/Family report (HoME‐CF) is a researcher‐rated interview which obtains client and/or family perspectives regarding frequency and valence of conversational and recreational engagement during care worker visits. Care workers ( n  = 84) completed the HoME‐S and a measure of relationship bond with client. Researchers interviewed clients ( n  = 164) and/or their family ( n  = 117) and completed the HoME‐CF, and measures of agitation, dysphoria, apathy and cognitive functioning. The HoME‐S and HoME‐CF demonstrated good test–retest and inter‐rater reliability, and showed significant negative correlations with apathy, agitation and non‐English‐speaking background. Controlling for client and care service characteristics, a stronger care worker–client relationship bond and English‐speaking background were independently associated with higher HoME‐S scores, and apathy was independently associated with higher HoME‐CF scores. In conclusion, the HoME‐S and HoME‐CF are psychometrically sound engagement measures for use in homecare. Clients who are apathetic or from non‐English‐speaking backgrounds may be less responsive to traditional care worker engagement strategies. Engagement may be augmented in clients who have stronger relationships with their care workers.